Удмурт театр: ортчем вамышъёс : очеркъёс / Б. Е. Саушкин - Саушкин Борис Ефремович (Удмуртия, 2000)
Экземпляры: КО (ретро) / Инвентарный номер: 35592 / Цена: / Сис.шифр: К85.33(2Рос.Удм) / Авт.знак: С 21 / ГРНТИ: 18.45 / ББК: 85.33(2Рос.Удм)